Frequent handling of grazing beef cattle maintained under the rotational stocking method improves temperament over time - Ceballos, Maria C. [UNESP]; Gois, Karen Camille R. [UNESP]; Sant'Anna, Aline C. [UNESP]; Paranhos da Costa, Mateus J. R. [UNESP] (Csiro Publishing, 2018)
Our aims were to assess the effects of handling frequency on temperament evolution in cattle kept under rotational stocking method (RSM), as well as to compare the temperament of animals maintained under rotational versus alternate stocking (ASM) methods. We evaluated 4256 males raised on pasture from four private properties (Farms 1-4), for a total of 9628 observations. The study was divided into two complementary approaches. In the first one, monthly visits were conducted at 35-day intervals to assess the cattle temperament (n = 1979) raised on grazing system using RSM, while, in the second approach, we evaluated the temperament of cattle (n = 3600) kept under two different stocking methods, namely, (1) RSM (n = 2007), characterised by a high frequency of animal handling and a 4-day grazing period, and (2) ASM (n = 1593), characterised by a low frequency of handling and a 20-day grazing period. Composite reactivity score (RS), and flight speed (FS) were considered as temperament indicators. Reductions of RS and FS means were observed during successive assessments under RSM. Significant effects of stocking method on FS (P < 0.05) and RS (P < 0.01) were found, with lower FS and RS means for animals under RSM than for those under ASM. In conclusion, the frequent handling in the rotational stocking method favoured the improvement of cattle temperament over time, with lower levels of reactivity among cattle raised under this stocking method than with animals raised under the alternate stocking method.
Keywords: animal behaviour; grazing management; stocking arrangement